Computational logistics : 10th International Conference, ICCL 2019, Barranquilla, Colombia, September 30-October 2, 2019, Proceedings /: 10th International Conference, ICCL 2019, Barranquilla, Colombia, September 30-October 2, 2019, Proceedings. (2019) - Unknown
No abstract available